Penyuluhan Dalam Upaya Pencegahan Stunting Oleh Mahasiswa Peserta Perguruan Tinggi Mandiri Gotong Royong Membangun Desa (PTMGRMD) - Hikmawati, Ikeu (Universitas Muhammadiyah Palembang, 2025)
KKNT PTMGRMD (Thematic Community Service Lecture for Independent Universities for Village Development) is a program that involves students from various universities including IPI GARUT, STIKES KARSA HUSADA GARUT, and STISIP SAMUDERA INDONESIA SELATAN to provide direct contributions to village development, which are placed in Cigadog village. The main objective of the KKNT PTMGRMD program is to improve the quality of life of the community through various empowerment programs, shape students into graduates who have high competence and social awareness, and build close relationships between the academic world and the community. This community service activity is carried out through health workshop activities, namely holding counseling on stunting prevention and how to overcome it to the community of Cigadog Village, Cikelet District, Garut Regency. This activity was carried out by KKNT PTMGRMD students, who collaborated with a team of health workers from the Cimari health center and village midwives. KKNT PTMGRMD students also conducted free health checks for the people of Cigadog village. This stunting counseling was attended by mothers and posyandu cadres who were greeted enthusiastically, because many of them still do not understand the symptoms of stunting and how to overcome it. In addition, by holding this stunting counseling, they become aware of the characteristics and causes, as well as how to overcome the symptoms of stunting. This stunting handling counseling was successfully carried out by KKNT PTMGRMD students in Cigadog Village and received a positive response from the local community.